Sinergi Pembangunan dalam Upaya Swasembada Garam Nasional (Studi Tentang Pelaksanaan Program Usaha Garam Rakyat di Kabupaten Pasuruan Provinsi Jawa Timur) - Ilyasa Suryaningpraja (Jurnal Administrasi Publik, 2015)
Abstract: The Development Synergy in The Attempt of National Salt Self-supporting (A Study about The Realization of Citizenry Salt Trade Program in Pasuruan Regency East Java). Indonesia as one of the largest maritime country in the world but still have to import salt so that needed a good development program. Pugar (the realization of citizenry salt trade empowerment program) is a national salt development program conducted in 40 district including Pasuruan. The existence of differences between development actors such as differences in interests, resources and skills it is necessary synergies in the implementation of Pugar. This research aims to analyze and describe the development synergy in the implementation Pugar in Pasuruan regency East Java and also the enabling and inhibiting factors in the program realization. The result of the research shows that has created a synergy in the implementation of Pugar because of the mutual trust, take and give and their creativity. The inhibiting factors in the Pugar program realization are the limited BLM (Bantuan Langsung Tunai), the culture of salt farmers known as â€œDaprokâ€, the uncertain weather and less institutional. While the enabling factors are the satisfactory support from all stakeholders to realize the purposes of Pasuruan regency Pugar program, well coordination and also the effective communication in the Pugar. This is an impotant need attention and special treatment from government so that this Pugar can effective with certaity and policy be valid. Keywords: Synergy, Development, Citizenry Salt Trade Empowerment Program (Pugar). Abstrak: Sinergi Pembangunan dalam Upaya Swasembada Garam Nasional (Studi tentang Pelaksanaan Program Usaha Garam Rakyat di Kabupaten Pasuruan Provinsi Jawa Timur). Indonesia sebagai salah satu negara maritim terbesar di dunia namun masih harus mengimpor garam sehingga diperlukan program pembangunan garam yang baik. Pugar (Pemberdayaan usaha garam rakyat) merupakan program pembangunan garam nasional yang dilakukan di 40 Kabupaten termasuk Kabupaten Pasuruan. Adanya berbagai perbedaan antar aktor pembangunan seperti perbedaan kepentingan, sumber daya dan ketrampilan maka diperlukan sinergi dalam pelaksanaan Pugar. Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan sinergi serta faktor-faktor pendukung dan penghambat dalam pelaksanaan Pugar di Kabupaten Pasuruan. Hasil penelitian menunjukkan telah tercipta sinergi dalam pelaksanaan Pugar karena adanya sikap saling percaya, take and give dan adanya kreatifitas. Faktor penghambat Pugar diantaranya keterbatasan dana BLM (Bantuan Langsung Tunai), budaya â€œdaprokâ€, ketidakpastian cuaca dan kurang maksimalnya kelembagaan. Faktor pendukungnya adalah koordinasi yang baik dan komunikasi efektif. Hal ini perlu mendapat perhatian dan tindakan dari pemerintah agar program Pugar berjalan efektif sesuai dengan ketentuan kebijakan yang berlaku. Â  Kata Kunci: Sinergi, Pembangunan, Program Pemberdayaan Usaha Garam Rakyat (Pugar).